Peran Landscape Dalam Kinerja Infrastruktur Perkotaan Studi kasus: Surabaya dan Malang, Indonesia - Ramdlani, Subhan; W, Lisa Dwi; Adhitama, M. Satya; Turningtyas, Turningtyas (Jurnal Ruas, 2013)
Transportation has been recognized as one of the indicators of this sector was instrumental in the development of the city . However , the development of transport seems to have the impact on the environment in the spatial and temporal large of coverage ( Rini , 2005) . The impact of high transport movements will contribute to the use of vehicle air pollution , thermal energy ( temperature ) and noise ( Soedomo , 1999). In Indonesia , stations , airports , public transport infrastructure and other terminals , has a noise level of up to 70 dB ( SK.MLH 24/11 , 1996) . The new urban design by Landscape Infrastructure is one of the strategies that extend the performance parameters of a landscape that is designed for high-performance multi - system function , including those originally thought to be derived from the traditional system infrastructure. Thinking in terms of Landscape Infrastructure adds several advantages to traditional infrastructure : the beauty of the city and re-vegetation/forestation , water and energy conservation ; restoration of natural systems , storm water management , agriculture, energy , expansion of wildlife habitat ; favored the use of pedestrians , and expanded parks and open space areas built ignored by the existing urban infrastructure ( Aquino , 2011) . This paper will discuss and how to optimize the design of the infrastructure landscape for urban transport infrastructure to minimize air pollution , noise and energy conservation, in terms of transport infrastructure in Malang and Surabaya , IndonesiaKeywords: Transportation, Landscapes, Infrastructure